Transformation of molecular compounds with Ba(Sr)/Al/Si and Ca(Sr, Ba)/Ti(Zr, Hf)/Si heteroelements as new efficient route to metal silicate materials. Issue 13 (12th March 2019) - Petrus, R.; Drąg-Jarząbek, A.; Utko, J.; Lis, T.; Sobota, P.
Abstract : The heterometallic alkoxides based on M–O–M′–O–Si motif were used for the preparation of ceramic materials consisting of mixed metal oxide nanocrystallites embedded in SiO2 matrix. Abstract : Silicon-based moieties were anchored in heterometallic alkoxide platforms to obtain molecular clusters based on the M–O–M′–O–Si motif for the generation of mixed-metal silicate materials. Single-source molecular precursors with structures [M(μ-ddbfo)2 Al(OSiPh3 )2 2 ], where dbbfoH = 2, 3-dihydro-2, 2-dimethylbenzofuran-7-ol and M = Ba (1 ), Sr (2 ), [Sr4 Ti2 (μ6 -O)(μ3, η 2 -OCH2 CH2 OMe)8 (η-OCH2 CH2 OMe)2 (OSiPh3 )4 ] (3 ), [Sr4 M′2 (μ4 -OH)(μ3, η 2 -OCH2 CH2 OMe)4 (μ, η 2 -OCH2 CH2 OMe)6 (μ-X)(OSiPh3 )4 ] (4, with M′ = Zr and X = Cl;5 with M′ = Hf and X = OH), [Sr3 Hf2 (μ5 -O)(μ3, η 2 -OCH2 CH2 OMe)4 (OCH2 CH2 OMe)4 (OSiPh3 )4 ] (6 ), and [Ca2 M′2 (μ3 -OH)2 (μ, η 2 -OCH2 CH2 OMe)4 (η 2 -HOCH2 CH2 OMe)2 (η-OCH2 CH2 OMe)2 (OSiPh3 )4 ] for M′ = Zr (7 ), Hf (8 ), were prepared by substitution of methyl groups, using Ph3 SiOH or chloride atoms with KOSiPh3, in [M(μ-ddbfo)2 AlMe2 2 ] (M = Sr, Ba) or [M4 M′2 (μ6 -O)(μ3, η 2 -OCH2 CH2 OMe)8 (OCH2 CH2 OMe)2 (HOCH2 CH2 OMe) x Cl4 ] (M = Ca, Sr, Ba, M′ = Ti, Zr, Hf and x = 0, 4). The precursors were characterized by elemental analysis, NMR spectroscopy, and single-crystal X-ray structural analysis. Thermal decomposition of compounds1–8 at 1000 °C led to formation of ceramic materials that consisted of mixed-metal oxide nanocrystallites embedded in an amorphous SiO2 matrix. Compounds1 and2 decomposed to BaAl2 Si2 O8 and SrAl2 Si2 O8 aluminosilicates, 4 gave a mixture of SrSiO3, ZrO2, SrZrO3 and Sr7 ZrSi6 O21, 5 and6 gave mixtures of various compounds, including SrHfO3, Hf0.96 Si0.04 O2, and SiO2, 7 lead to CaZrO3, ZrO2 and Ca3 ZrSi2 O9 and8 gave a HfO2, Ca2 HfSi4 O12 and SiO2 phase. The thermolysis of compound3 gave SiO2 particles of average size 40–90 nm, which contained spherical SrTiO3, SrSiO3 and Sr2 TiSi2 O8 nanocrystallites of diameter 5–16 nm.